The Road to Scottish Dominican Independence 1230–1511 - Op, Allan James White (New blackfriars, 2021)
In 1221 the General Chapter of the Order of Preachers (Dominican friars) sent out groups of friars to various European countries. The largest group was sent to England where they established their first priory in the University city of Oxford on the Feast of the Assumption, 1221. Within a decade they had spread to Ireland and has established their first houses in Scotland. The Scottish Dominicans remained part of the English province for close on 300 years. The Scottish Wars of Independence forced a reconsideration of that relationship. In 1481 Scotland became an independent province and adopted the Strict Observance initiated by Raymond of Capua (1330-1399). The province flourished for the first sixty years of its existence before being overwhelmed by the Scottish Reformation.